A shock-resistant clad structure wave-absorbing ceramic composite and a preparation method thereof

CN122458398BActive Publication Date: 2026-09-08REFRACTORY MATERIAL OF SINOSTEEL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610920956.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-09-08
Estimated Expiration
2046-06-25

AI Technical Summary

Technical Problem

然而,现有的复合吸波陶瓷体多关注电磁性能的优化,而对工程应用中的环境适应性和力学保护考虑不足,陶瓷材料本身固有的脆性使其难以承受环境中的雨蚀、沙尘撞击或其他冲击,结构易损伤,导致吸波功能失效;若单纯提高陶瓷基体的力学强度,其过高的介电常数可能导致表面波阻抗严重失配,入射波大量反射,吸波性能下降;若专注于优化吸波填料的性能,其基体往往强度不足,抗冲击性能差

Benefits of technology

[0030]本发明采用“透波高强外壳+吸波夹芯内层”的包层结构设计,从根本上解决了吸波材料力学性能不足的难题。高强韧的外层Si3N4陶瓷壳作为盔甲,抵御物理冲击;内层吸波材料专注实现电磁损耗,二者通过电磁波透射/吸收的物理过程协同工作,实现了抗冲击与吸波的统一防护。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122458398B_ABST
    Figure CN122458398B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of functional ceramic materials, and discloses a shock-resistant cladding structure wave-absorbing ceramic composite and a preparation method thereof. The composite is a hard shell-sandwich structure, the outer layer is a high-strength and high-toughness Si3N4 ceramic shell, and the inner layer is a wave-absorbing sandwich layer filled in the Si3N4 ceramic shell. The sandwich layer is combined with a porous ceramic matrix, a resin matrix or a porous structure itself by using a worm-like / whisk-like composite β-SiC nanometer material, and absorbs radar waves transmitted through the Si3N4 ceramic shell. The cladding structure of the application adopts an optimized combination of different material layers, uses the worm-like / whisk-like composite β-SiC nanometer wave-absorbing material, and the optimized morphology and proportion ensure wide frequency and high-efficiency dielectric loss. In combination with the excellent high-temperature strength, fracture toughness and thermal shock resistance of the ceramic shell, the application has outstanding shock resistance, so that the whole composite can withstand severe mechanical and thermal shock environments, and effectively isolate environmental corrosion factors such as water vapor and salt, thereby protecting the performance stability of the internal wave-absorbing functional material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional ceramic materials technology, specifically relating to an impact-resistant cladding structure for absorbing ceramic composites and its preparation method. Background Technology

[0002] Microwave-absorbing materials, which effectively reduce the reflection of incident electromagnetic waves and absorb them through various attenuation mechanisms, are widely used in protecting human health and in precision electronic equipment and stealth technology. The most effective measure to control electromagnetic radiation is electromagnetic shielding, whose main purpose is to prevent the influence of radio frequency electromagnetic waves and control their radiation intensity within a harmless range for the human body. The performance requirements for microwave absorbers are becoming increasingly stringent, requiring not only wide-bandwidth, strong absorption electromagnetic characteristics, but also meeting the complex engineering application environment requirements such as weather resistance, thermal shock resistance, load-bearing capacity, and corrosion resistance.

[0003] SiC, as a typical dielectric ceramic material, is considered one of the most promising microwave absorbing materials due to its excellent dielectric properties, high-temperature stability, excellent chemical stability, and lightweight characteristics. While SiC is considered one of the most promising microwave absorbing materials because of its excellent physicochemical properties, its single attenuation mechanism results in less than ideal absorption performance, making it difficult to meet the diverse requirements of modern high-efficiency microwave absorbing materials. Generally, microstructure and structure have a significant impact on absorption performance; designing special morphologies and structures can significantly affect absorption performance. Special structures (porous, hollow, and core-shell) can optimize the dielectric constant, thereby improving impedance matching and allowing more electromagnetic waves to enter the interior of the absorbing material and be attenuated, thus improving absorption performance. Furthermore, these special structures can introduce a large number of interfaces, enhancing the interfacial polarization effect and further improving absorption performance. Composite microwave absorbing structures, by designing layers with different electromagnetic parameters, achieve a gradual impedance change from free space to a metallic backing, thereby improving absorption bandwidth and efficiency. However, existing composite absorbing ceramic bodies mostly focus on optimizing electromagnetic performance, while neglecting environmental adaptability and mechanical protection in engineering applications. The inherent brittleness of ceramic materials makes them difficult to withstand rain erosion, sand and dust impacts, or other shocks in the environment, and the structure is easily damaged, leading to the failure of the absorbing function. If the mechanical strength of the ceramic matrix is ​​simply increased, its excessively high dielectric constant may lead to a serious mismatch in surface wave impedance, resulting in a large amount of incident wave reflection and a decrease in absorbing performance. If the focus is on optimizing the performance of the absorbing filler, its matrix often has insufficient strength and poor impact resistance.

[0004] Therefore, developing a radar-absorbing ceramic composite that can achieve both efficient radar wave absorption and excellent shock resistance has become a pressing technical challenge in this field. Summary of the Invention

[0005] In order to solve the above-mentioned technical problems, this invention addresses the shortcomings of existing microwave absorbing ceramic bodies in terms of weather resistance, impact resistance, and multifunctional collaborative design. It adopts a microwave absorbing ceramic composite with an impact-resistant cladding structure, which significantly improves the impact resistance while ensuring microwave absorption performance, and achieves a deep integration of microwave absorption function with the needs of practical engineering applications.

[0006] To achieve the above objectives, the technical solution adopted in this invention is as follows: an impact-resistant cladding structure for absorbing ceramic composites, wherein the composite is a hard shell-sandwich structure, the outer layer being a high-strength and high-toughness Si3N4 ceramic shell; the inner layer being an absorbing sandwich layer filled inside the outer Si3N4 ceramic shell, wherein the sandwich layer uses worm-like / whisker-like composite β-SiC nanomaterials as the absorbing functional phase, and is composited in a porous ceramic matrix, resin matrix, or the porous structure itself, to absorb radar waves that pass through the outer Si3N4 ceramic shell.

[0007] The raw materials for the outer Si3N4 ceramic shell, by weight, include: 90-95 parts α-Si3N4 powder, 1-5 parts Si3N4 whiskers or 1-3 parts short-cut boron nitride fibers; 2-5 parts Y2O3, 2-3 parts Al2O3, and 1-2 parts MgO.

[0008] The α-phase content of the α-Si3N4 powder is ≥92%, and the particle size is 0.5~1.0μm.

[0009] The outer Si3N4 ceramic shell incorporates Si3N4 whiskers or short-cut boron nitride fibers as a toughening phase to further enhance toughness and wave transmission. Y2O3, Al2O3, and MgO are added as composite sintering aids to form a high-temperature refractory grain boundary phase, avoiding excessive low-melting glass phase that leads to high-temperature strength decay and increased dielectric loss.

[0010] The raw materials of the microwave absorbing sandwich layer, by weight, include: 35-45 parts of worm-like / whisker-like composite β-SiC nanomaterials, 45-55 parts of mullite powder, 2-3 parts of Y2O3, 1-2 parts of Al2O3, 2-4 parts of polyvinyl alcohol, and 4-7 parts of ethanol or isopropanol; plus deionized water containing 0.5-2 wt% ammonium polyacrylate dispersant, 1.0-3.0 wt% hydroxyethyl cellulose as a binder, and 1.0-2.0 wt% glycerol as a plasticizer.

[0011] The β-SiC nano-absorbing material is made from a mixture of nano-amorphous silica and nano-carbon black in a mass ratio of 1:3 as raw materials; a platinum-rhodium metal mixture accounting for 1-3% of the total weight of the raw materials is added as a catalyst; and the worm-like and whisker-like composite β-SiC nano-absorbing material is obtained by sintering at 2200℃ under the protection of inert argon gas; the mass ratio of platinum to rhodium in the platinum-rhodium metal mixture is 3:7 to 7:3.

[0012] The addition of Y2O3 and Al2O3 as composite sintering aids to the microwave absorbing sandwich layer can form YAG(Y3Al5O3)2O3. 12 It can be a liquid phase of yttrium aluminum silicate, which promotes the bonding of mullite and SiC, and is resistant to high temperature and chemically stable.

[0013] A method for preparing an impact-resistant cladding structure microwave absorbing ceramic composite includes the following steps:

[0014] Step 1: Preparation of the outer Si3N4 ceramic shell:

[0015] S1. Ingredients: Weigh out α-Si3N4 powder, Si3N4 whiskers or short-cut boron nitride fibers, Y2O3, Al2O3, and MgO according to the proportions.

[0016] S2. Ball milling and mixing: Place the above powder into a nylon can, use anhydrous ethanol as the medium and zirconia balls as the milling medium, and ball mill for 12 hours; then dry in an 80℃ oven and pass through an 80-mesh sieve.

[0017] S3. Molding: The sieved mixed powder is loaded into a rubber mold and pressed under 220MPa pressure for 5 minutes by a cold isostatic press to obtain the outer Si3N4 ceramic shell blank.

[0018] S4. Pre-sintering: The green body is placed in an atmosphere sintering furnace and heated to 1800℃ at 5℃ / min under a nitrogen pressure of 0.5MPa. It is held for 3 hours and then cooled with the furnace to obtain the outer Si3N4 ceramic shell.

[0019] Step 2: Preparation of the microwave absorbing sandwich layer slurry:

[0020] S1. Preparation of microwave absorbing material: Weigh the raw amorphous nano-silica and nano-carbon black at a mass ratio of 1:3 and mix them evenly. Place them in a mixer and mix them thoroughly at 80-120 r / min for 4-6 h. Then add the catalyst and continue mixing until uniform. Place the mixture in the crucible of a high-temperature reaction device, introduce argon gas as a protective gas, and heat it to 2200℃ at a heating rate of 10-20℃ / min. Keep it at this temperature for 14-16 h. After the reaction is completed, cool it naturally to room temperature under the protection of argon atmosphere. Take out the product, crush it, sieve it, and remove impurities to obtain worm-like / whisker-like composite β-SiC nanomaterials. The mass percentage ratio of whisker-like structure to worm-like structure in the β-SiC nano-absorbing material is (60-70):(30-40).

[0021] S2. Raw material preparation: Weigh out the worm-like / whisker-like composite β-SiC nanomaterials, mullite powder, Y2O3 and Al2O3 micro powders according to the proportion;

[0022] S3. Slurry dispersion: Add the above raw materials to deionized water containing 0.5-2 wt% ammonium polyacrylate dispersant, mix evenly, and control the solid content at 35-45 wt%.

[0023] S4. Adding additives: Add 1.0 to 3.0 wt% of hydroxyethyl cellulose as a binder and 1.0 to 2.0 wt% of glycerol as a plasticizer. Stir for 2 hours and then degas under vacuum to obtain the microwave absorbing sandwich layer slurry with a viscosity of 300 to 3000 mPa·s.

[0024] Step 3: Interlayer coating and drying:

[0025] The inner surface of the outer Si3N4 ceramic shell obtained in step one is roughened by sandblasting. Then, the microwave absorbing sandwich layer slurry obtained in step two is uniformly coated onto the inner side of the shell by screen printing. The coating is applied in multiple layers, with each layer having a thickness of 0.2 to 0.5 mm, and the coating thickness is controlled at 1.5 to 2 mm. After coating, the shell is dried at room temperature for 12 hours and then placed in a constant temperature oven at 60 to 80°C for slow drying for 6 to 10 hours to prevent cracking due to uneven shrinkage of the inner and outer layers.

[0026] Step 4: Final sintering

[0027] The dried double-layer green body is placed in a sintering furnace and heated to 300–450°C in air at a rate of 1–5°C / min, and held for 2–4 hours to completely remove the organic binder. After the binder is removed, the air inlet valve is closed, and an inert gas is introduced as a protective atmosphere. The temperature is then increased to 1800°C at a rate of 5–20°C / min and held for 2–4 hours. The green body is then cooled in the furnace to below 200°C and removed from the furnace. It is then allowed to cool naturally to room temperature, forming a microwave absorbing ceramic composite with a cladding structure consisting of an outer Si3N4 ceramic shell and a microwave absorbing core layer.

[0028] The mechanical properties of the microwave absorbing ceramic composite are: flexural strength ≥ 850 MPa, fracture toughness ≥ 7.0 MPa·m. 1 / 2 Impact resistance ≥40J / cm²; Electromagnetic performance: Reflectivity below -25.0dB in the 8-12GHz (X-band) frequency range, effective absorption bandwidth ≥3.0GHz; Outer layer transmittance 90.5%. Weather resistance: After 500 hours of neutral salt spray test, the surface shows no rust or delamination, and the absorption performance decreases by <1dB.

[0029] After undergoing a standard fragment impact test, the outer shell of the microwave-absorbing ceramic composite did not suffer penetrating damage and the structure remained intact. The microwave absorption curves before and after the impact test were basically the same, indicating that its stealth function was well maintained after being subjected to a certain mechanical impact.

[0030] This invention employs a cladding structure design of "high-strength, wave-transmitting outer shell + wave-absorbing inner core," fundamentally solving the problem of insufficient mechanical properties of wave-absorbing materials. The high-strength and tough outer Si3N4 ceramic shell acts as armor, resisting physical impacts; the inner wave-absorbing material focuses on electromagnetic loss. The two work synergistically through the physical process of electromagnetic wave transmission / absorption, achieving unified protection against impact and wave absorption.

[0031] The shock-resistant cladding structure of the microwave-absorbing ceramic composite prepared in this invention exhibits excellent comprehensive performance: 1. Superior absorption performance: The core adopts a worm-like / whisker-like composite β-SiC nano-absorbing material. Its optimized morphology and proportion ensure wide-bandwidth and high-efficiency dielectric loss. The whisker-like structure constructs a conductive network, which is beneficial for conduction loss and multiple reflection and scattering; the worm-like structure introduces a large number of interfaces, defects, and dipoles, enhancing interface polarization and dipole polarization loss. The combination of the two achieves complementarity and synergy in the loss mechanism, enabling the material to have high absorption efficiency over a wide frequency band. Combined with the transparent shell design, the absorption frequency band is further broadened and the reflectivity is reduced; 2. Significantly improved environmental durability: The outer layer adopts a dense Si3N4 ceramic shell, which can effectively isolate environmental corrosion factors such as water vapor and salt, protecting the long-term stability of the internal microwave-absorbing functional material. 3. Outstanding impact resistance: Utilizing the excellent high-temperature strength, fracture toughness, and thermal shock resistance of the outer Si3N4 ceramic shell, the entire composite can withstand harsh mechanical and thermal shock environments; 4. Flexible structure and wide application: It can be selected and its parameters adjusted according to specific application scenarios, such as the requirements for mechanical strength and stealth frequency bands, and is suitable for various stealth platforms such as aircraft skin, ship components, ground equipment shells, and radomes.

[0032] To balance impedance matching and loss performance, the preferred mass percentage of the fibrous structure to the worm-like structure in the β-SiC nanomaterial is (60-70):(30-40); the preferred reaction time range corresponding to this ratio is 14-16 hours.

[0033] The beneficial effects of this invention are as follows: The cladding structure of this invention is achieved through the optimized combination of different material layers. The internal absorbing core layer adopts worm-like / whisker-like composite β-SiC nano-absorbing material, and its optimized morphology and proportion ensure wide-bandwidth and high-efficiency dielectric loss. Combined with the excellent high-temperature strength, fracture toughness and thermal shock resistance of the outer Si3N4 ceramic shell, it has outstanding impact resistance, enabling the entire absorbing ceramic composite to withstand harsh mechanical and thermal shock environments, and effectively isolate environmental corrosion factors such as water vapor and salt, protecting the performance stability of the internal absorbing functional materials. It can be applied in the fields of aerospace and high-end electronic equipment. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the cladding structure microwave absorbing ceramic composite of the present invention;

[0035] Figure 2 The image shows the microwave absorption performance of the cladding structure microwave absorbing ceramic composite prepared in Example 1 of this invention.

[0036] Figure 3 The image shows the microwave absorption performance of the cladding structure microwave absorbing ceramic composite prepared in Example 2 of this invention.

[0037] Figure 4 The image shows the microwave absorption performance of the cladding structure microwave absorbing ceramic composite prepared in Example 3 of this invention.

[0038] The diagram shows: 1. Absorbing core layer; 2. Outer Si3N4 ceramic shell. Detailed Implementation

[0039] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.

[0040] Example 1:

[0041] A method for preparing an impact-resistant cladding structure microwave absorbing ceramic composite includes the following steps:

[0042] Step 1: Preparation of the outer Si3N4 ceramic shell:

[0043] Weigh out 92 parts by weight of α-Si3N4 powder, 3 parts of Si3N4 whiskers, 3.5 parts of Y2O3, 2.5 parts of Al2O3, and 1.5 parts of MgO; place them in a nylon can and ball mill them for 12 hours using anhydrous ethanol as the medium and zirconia balls as the grinding medium. Then dry them in an 80°C oven and pass them through an 80-mesh sieve. Load the sieved mixed powder into a rubber mold and press it under 220 MPa pressure for 5 minutes using a cold isostatic press. Then place it in an atmosphere sintering furnace and heat it to 1800°C at 5°C / min under 0.5 MPa nitrogen pressure. Hold it at that temperature for 3 hours and cool it with the furnace to obtain the outer Si3N4 ceramic shell.

[0044] Step 2: Preparation of the microwave absorbing sandwich layer slurry:

[0045] The raw materials, amorphous nano-silica and nano-carbon black, were weighed and mixed evenly at a mass ratio of 1:3. Platinum-rhodium metal ultrafine powder catalyst, accounting for 1.5% of the total weight of the raw materials, was added and placed in a high-temperature reaction device. Argon gas was introduced and the temperature was raised to 2200℃ at a heating rate of 15℃ / min. The temperature was then maintained at this temperature for 14 hours, and sintering was performed to obtain worm-like / whisker-like composite β-SiC nanomaterials, wherein the mass percentage ratio of whisker-like structure to worm-like structure was 60:40.

[0046] By weight, 40 parts of worm-like / whisker-like composite β-SiC nanomaterials, 50 parts of mullite powder, 2.5 parts of Y2O3 and 1.5 parts of Al2O3 were weighed and mixed evenly; then, they were dispersed in deionized water containing 1 wt% ammonium polyacrylate, with a solid solution content of 40 wt%; 1.5 wt% hydroxyethyl cellulose and 1.0 wt% glycerol were added according to the total weight of the raw materials, and after stirring for 2 hours, vacuum degassing was performed to obtain the microwave absorbing sandwich layer slurry with a viscosity of 1500 mPa·s;

[0047] Step 3: Interlayer coating and drying:

[0048] The inner surface of the outer Si3N4 ceramic shell was roughened by sandblasting. The microwave absorbing sandwich layer paste obtained in step two was screen-printed onto the inner surface of the outer Si3N4 ceramic shell in four coats, each coat being 0.4 mm thick, for a total thickness of 1.6 mm. After coating, the shell was dried at room temperature for 12 hours and then placed in a 60°C constant temperature oven for slow drying for 8 hours.

[0049] Step 4: Final sintering

[0050] The dried double-layer green body is placed in a sintering furnace and heated to 400°C at a rate of 2°C / min in air. After holding at this temperature for 3 hours, the binder is removed. The air inlet valve is closed, and argon gas is introduced as a protective atmosphere. The temperature is then increased to 1800°C at a rate of 10°C / min and held for 3 hours. The green body is then cooled in the furnace to below 200°C and removed from the furnace. It is then allowed to cool naturally to room temperature and then cooled in the furnace again to obtain a microwave absorbing ceramic composite with a cladding structure consisting of an outer Si3N4 ceramic shell and a microwave absorbing sandwich layer.

[0051] Example 2:

[0052] A method for preparing an impact-resistant cladding structure microwave absorbing ceramic composite includes the following steps:

[0053] Step 1: Preparation of the outer Si3N4 ceramic shell:

[0054] Weigh out 92 parts by weight of α-Si3N4 powder, 3 parts by weight of short boron nitride fiber, 5 parts by weight of Y2O3, 2 parts by weight of Al2O3, and 1 part by weight of MgO. Place them in a nylon can and ball mill them for 12 hours using anhydrous ethanol as the medium and zirconia balls as the grinding medium. Then dry them in an 80°C oven and pass them through an 80-mesh sieve. Load the sieved mixed powder into a rubber mold and press it under 220MPa pressure for 5 minutes using a cold isostatic press. Then place it in an atmosphere sintering furnace and heat it to 1800°C at 5°C / min under 0.5MPa nitrogen pressure. Hold it at that temperature for 3 hours and cool it with the furnace to obtain the outer Si3N4 ceramic shell.

[0055] Step 2: Preparation of the microwave absorbing sandwich layer slurry:

[0056] The raw materials, amorphous nano-silica and nano-carbon black, were weighed and mixed evenly at a mass ratio of 1:3. Platinum-rhodium metal ultrafine powder catalyst, accounting for 1% of the total weight of the raw materials, was added and placed in a high-temperature reaction device. Argon gas was introduced and the temperature was raised to 2200℃ at a heating rate of 10℃ / min. The temperature was then maintained at this temperature for 16 hours, and sintering was performed to obtain worm-like / whisker-like composite β-SiC nanomaterials, wherein the mass percentage ratio of whisker-like structure to worm-like structure was 70:30.

[0057] By weight, 45 parts of worm-like / whisker-like composite β-SiC nanomaterials, 48 ​​parts of mullite powder, 3 parts of Y2O3 and 2 parts of Al2O3 were weighed and mixed evenly; then, deionized water containing 0.5 wt% ammonium polyacrylate was added and dispersed, with a solid solution content of 35 wt%; 1 wt% hydroxyethyl cellulose and 1 wt% glycerol were added according to the total weight of raw materials, and after stirring for 2 hours, vacuum degassing was performed to obtain the microwave absorbing sandwich layer slurry with a viscosity of 300 mPa·s;

[0058] Step 3: Interlayer coating and drying:

[0059] The inner surface of the outer Si3N4 ceramic shell was roughened by sandblasting. The microwave absorbing sandwich layer paste obtained in step two was screen-printed onto the inner surface of the outer Si3N4 ceramic shell in 5 layers, with each layer having a thickness of 0.4 mm and a total thickness of 2.0 mm. After coating, the shell was dried at room temperature for 12 hours and then placed in a 60℃ constant temperature oven for slow drying for 8 hours.

[0060] Step 4: Final sintering

[0061] The dried double-layer green body is placed in a sintering furnace and heated to 300°C at a rate of 1°C / min in air. It is held at this temperature for 4 hours to remove the binder. The air inlet valve is closed, and argon gas is introduced as a protective atmosphere. The temperature is then increased to 1800°C at a rate of 5°C / min and held for 2 hours. The green body is then cooled in the furnace to below 200°C and removed from the furnace. It is then allowed to cool naturally to room temperature and then cooled in the furnace again to obtain a microwave absorbing ceramic composite with a cladding structure consisting of an outer Si3N4 ceramic shell and a microwave absorbing sandwich layer.

[0062] Example 3:

[0063] A method for preparing an impact-resistant cladding structure microwave absorbing ceramic composite includes the following steps:

[0064] Step 1: Preparation of the outer Si3N4 ceramic shell:

[0065] Weigh out 90 parts by weight of α-Si3N4 powder, 5 parts of Si3N4 whiskers, 3 parts of Y2O3, 3 parts of Al2O3, and 2 parts of MgO; place them in a nylon can and ball mill them for 12 hours using anhydrous ethanol as the medium and zirconia balls as the grinding medium. Then dry them in an 80℃ oven and pass them through an 80-mesh sieve. Load the sieved mixed powder into a rubber mold and press it under 220MPa pressure for 5 minutes using a cold isostatic press. Then place it in an atmosphere sintering furnace and heat it to 1800℃ at 5℃ / min under 0.5MPa nitrogen pressure. Hold it at that temperature for 3 hours and cool it with the furnace to obtain the outer Si3N4 ceramic shell.

[0066] Step 2: Preparation of the microwave absorbing sandwich layer slurry:

[0067] The raw materials, amorphous nano-silica and nano-carbon black, were weighed and mixed evenly at a mass ratio of 1:3. Platinum-rhodium metal ultrafine powder catalyst, accounting for 3% of the total weight of the raw materials, was added and placed in a high-temperature reaction device. Argon gas was introduced and the temperature was raised to 2200℃ at a heating rate of 20℃ / min. The temperature was then maintained at this temperature for 15 hours, and sintering was performed to obtain worm-like / whisker-like composite β-SiC nanomaterials, wherein the mass percentage ratio of whisker-like structure to worm-like structure was 65:35.

[0068] By weight, 35 parts of worm-like / whisker-like composite β-SiC nanomaterials, 55 parts of mullite powder, 2 parts of Y2O3 and 1 part of Al2O3 were weighed and mixed evenly; then, they were dispersed in deionized water containing 2wt% ammonium polyacrylate, with a solid solution content of 45wt%; 3wt% hydroxyethyl cellulose and 2wt% glycerol were added according to the total weight of the raw materials, and after stirring for 2 hours, vacuum degassing was performed to obtain the microwave absorbing sandwich layer slurry with a viscosity of 3000 mPa·s;

[0069] Step 3: Interlayer coating and drying:

[0070] The inner surface of the outer Si3N4 ceramic shell was roughened by sandblasting. The microwave absorbing sandwich layer paste obtained in step two was screen-printed onto the inner surface of the outer Si3N4 ceramic shell in 6 layers, with each layer having a thickness of 0.3 mm and a total thickness of 1.8 mm. After coating, it was dried at room temperature for 12 hours and then placed in a constant temperature oven at 60℃ for slow drying for 8 hours.

[0071] Step 4: Final sintering

[0072] The dried double-layer green body is placed in a sintering furnace and heated to 450°C at a rate of 5°C / min in air. After holding at this temperature for 2 hours, the binder is removed. The air inlet valve is closed, and argon gas is introduced as a protective atmosphere. The temperature is then increased to 1800°C at a rate of 20°C / min and held for 4 hours. The green body is then cooled in the furnace to below 200°C and removed from the furnace. It is then allowed to cool naturally to room temperature and then cooled in the furnace again to obtain a microwave absorbing ceramic composite with a cladding structure consisting of an outer Si3N4 ceramic shell and a microwave absorbing sandwich layer.

[0073] Table 1. Main performance indicators of the cladding structure microwave absorbing ceramic composites prepared in Examples 1-3

[0074]

[0075] like Figure 1 As shown, the cladding structure of the microwave absorbing ceramic composite consists of an outer Si3N4 ceramic shell 2 covering the outside of the microwave absorbing core layer 1. Through ingenious process design, the microwave absorbing core layer 1 utilizes worm-like / whisker-like composite β-SiC nanomaterials with adjustable morphology ratios, which exhibit superior performance as a microwave absorbing filler. The outer Si3N4 ceramic shell 2 possesses excellent high-temperature strength, fracture toughness, and thermal shock resistance, and demonstrates outstanding impact resistance. Table 1 shows that the mechanical properties of this microwave absorbing ceramic composite are: flexural strength ≥ 850 MPa, fracture toughness ≥ 7 MPa·m. 1 / 2 Impact resistance ≥40J / cm². Electromagnetic performance: Reflectivity below -25.0dB in the 8-12GHz (X-band) frequency range, effective absorption bandwidth ≥3.0GHz; outer layer transmittance 90.5%. Weather resistance: After 500 hours of neutral salt spray testing, the surface shows no rust or delamination, and the absorption performance decreases by <1dB. After undergoing a standard fragment impact test, the outer shell of this absorbing ceramic composite did not suffer penetrating damage, and the structure remained intact; the absorption curves before and after the impact test basically overlapped, indicating that its stealth function was well maintained after withstanding a certain amount of mechanical impact. The entire cladding structure of the absorbing ceramic composite can withstand harsh mechanical and thermal shock environments and effectively isolates environmental corrosion factors such as water vapor and salt, protecting the performance stability of the internal absorbing functional materials, and has good prospects for industrial applications.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A microwave absorbing ceramic composite with an impact-resistant cladding structure, characterized in that: The composite is a hard shell-sandwich structure, with an outer layer of Si3N4 ceramic shell and an inner layer of microwave absorbing sandwich layer filled inside the outer Si3N4 ceramic shell. The sandwich layer uses worm-like / whisker-like composite β-SiC nanomaterials as the microwave absorbing functional phase, which is composited in a porous ceramic matrix, resin matrix or porous structure itself to absorb radar waves that pass through the outer Si3N4 ceramic shell. By weight, the raw materials for the outer Si3N4 ceramic shell include: 90-95 parts of α-Si3N4 powder, 1-5 parts of Si3N4 whiskers or 1-3 parts of short-cut boron nitride fibers; 2-5 parts of Y2O3, 2-3 parts of Al2O3, and 1-2 parts of MgO. By weight, the raw materials of the microwave absorbing sandwich layer include: 35-45 parts of worm-like / whisker-like composite β-SiC nanomaterials, 45-55 parts of mullite powder, 2-3 parts of Y2O3, 1-2 parts of Al2O3, 2-4 parts of polyvinyl alcohol, and 4-7 parts of ethanol or isopropanol; deionized water containing 0.5-2 wt% ammonium polyacrylate dispersant, with the solid solution content controlled at 35-45 wt%; 1.0-3.0 wt% of hydroxyethyl cellulose as a binder and 1.0-2.0 wt% of glycerol as a plasticizer. In the worm-like / whisker-like composite β-SiC nano-absorbing material, the mass percentage ratio of whisker-like structure to worm-like structure is (60-70): (30-40).

2. The wave-absorbing ceramic composite with an impact-resistant cladding structure according to claim 1, characterized in that: The worm-like / whisker-like composite β-SiC nanomaterials are made from a mixture of nano-sized amorphous silica and nano-carbon black in a mass ratio of 1:3; a platinum-rhodium metal mixture accounting for 1-3% of the total weight of the raw materials is added as a catalyst; the mass ratio of platinum to rhodium in the platinum-rhodium metal mixture is 3:7 to 7:

3.

3. The wave-absorbing ceramic composite with an impact-resistant cladding structure according to claim 1, characterized in that: The α-phase content in the α-Si3N4 powder is ≥92%, and the particle size is 0.5~1.0μm.

4. A method for preparing a microwave absorbing ceramic composite with an impact-resistant cladding structure as described in claim 1, characterized in that, Includes the following steps: Step 1: Preparation of the outer Si3N4 ceramic shell: S1. Ingredients: Weigh out α-Si3N4 powder, Si3N4 whiskers or short-cut boron nitride fibers, Y2O3, Al2O3, and MgO according to the proportions. S2. Ball milling and mixing: Place the above materials in a nylon can and ball mill for 12 hours using anhydrous ethanol as the medium and zirconia balls as the milling medium; then dry in an 80°C oven and pass through an 80-mesh sieve. S3. Molding: The sieved mixed powder is loaded into a rubber mold and pressed under 220MPa pressure for 5 minutes by a cold isostatic press to obtain the outer Si3N4 ceramic shell blank. S4. Pre-sintering: The green body is placed in an atmosphere sintering furnace and heated to 1800℃ at 5℃ / min under a nitrogen pressure of 0.5MPa. It is held for 3 hours and then cooled with the furnace to obtain the outer Si3N4 ceramic shell. Step 2: Preparation of the microwave absorbing sandwich layer slurry: S1. Preparation of microwave absorbing material: The raw amorphous nano-silica and nano-carbon black are weighed and mixed evenly at a mass ratio of 1:

3. The mixture is placed in a mixer and thoroughly mixed at 80-120 r / min for 4-6 h. The catalyst is then added and the mixture is continued until uniform. The mixture is placed in a crucible of a high-temperature reaction device and argon gas is introduced for protection. The mixture is then sintered at high temperature. The sintering temperature is increased to 2200℃ at a heating rate of 10-20℃ / min and held at this temperature for 14-16 h. After the reaction is completed, the mixture is naturally cooled to room temperature under the protection of argon atmosphere. The product is then taken out and, after crushing, sieving, and impurity removal, worm-like / whisker-like composite β-SiC nanomaterials are obtained. S2. Raw material preparation: Weigh out the worm-like / whisker-like composite β-SiC nanomaterials, mullite powder, Y2O3 and Al2O3 micro powders according to the proportion; S3. Slurry dispersion: Add the above raw materials to deionized water containing 0.5-2 wt% ammonium polyacrylate dispersant, mix evenly, and control the solid content at 35-45 wt%. S4. Adding additives: Add 1.0 to 3.0 wt% of hydroxyethyl cellulose as a binder and 1.0 to 2.0 wt% of glycerol as a plasticizer. Stir for 2 hours and then degas under vacuum to obtain the microwave absorbing sandwich layer slurry with a viscosity of 300 to 3000 mPa·s. Step 3: Interlayer coating and drying: The inner surface of the outer Si3N4 ceramic shell obtained in step one is roughened by sandblasting. Then, the microwave absorbing sandwich layer slurry obtained in step two is uniformly coated onto the inner side of the shell by screen printing. The coating is applied in multiple layers, with each layer having a thickness of 0.2 to 0.5 mm, and the coating thickness is controlled at 1.5 to 2 mm. After coating, the shell is dried at room temperature for 12 hours and then placed in a constant temperature oven at 60 to 80°C for slow drying for 6 to 10 hours to prevent cracking due to uneven shrinkage of the inner and outer layers. Step 4: Final sintering The dried double-layer green body is placed in a sintering furnace and heated to 300-450°C at a rate of 1-5°C / min in air, and held for 2-4 hours to completely remove the organic binder. After the binder is removed, the air inlet valve is closed, and an inert gas is introduced as a protective atmosphere. The temperature is then increased to 1800°C at a rate of 5-20°C / min and held for 2-4 hours. The green body is then cooled to below 200°C in the furnace and removed from the furnace. It is then allowed to cool naturally to room temperature, forming a microwave absorbing ceramic composite with a cladding structure consisting of an outer Si3N4 ceramic shell and a microwave absorbing core layer.

5. The method for preparing an impact-resistant cladding structure microwave absorbing ceramic composite according to claim 4, characterized in that: The mechanical properties of the microwave absorbing ceramic composite are: flexural strength ≥ 850 MPa, fracture toughness ≥ 7.0 MPa·m. 1 / 2 Impact resistance ≥40J / cm²; Electromagnetic properties: reflectivity below -25.0dB in the 8-12GHz frequency range, effective absorption bandwidth ≥3.0GHz; Outer layer transmittance 90.5%; Weather resistance: After 500 hours of neutral salt spray test, the surface shows no rust or delamination, and the microwave absorption performance decreases by <1dB.

Citation Information

Patent Citations

  • Resistance loss type electromagnetic shielding material with core-shell structure and preparation method of resistance loss type electromagnetic shielding material

    CN117363011A

  • Composite wave-absorbing material with core-shell structure and preparation method of composite wave-absorbing material

    CN117511501A